Quantificação de citocinas no soro e homogenato da pata na intoxicação experimental com veneno de Bothropoides jararaca em ratos Wistar tratados com soroterapia e Mikania glomerata - Motta, Y.p.; Sakate, M.; Nogueira, R.m.b.; Peraçoli, M.t.s.; Sangiorgio, F.; Floriano, R.s.; Takahagi, E.n. (Universidade Federal de Minas Gerais, Escola de Veterinária, 2014)
This experiment aimed to quantify the pro-inflammatory cytokine levels, including TNF-α, interleukin-1β (IL-1β) and IL-6 as well as the anti-inflammatory ones such as IL-10 and INF-γ. It was also proposed to compare the effect of the conventional treatment to a treatment in which was added the Mikania glomerata plant in the experimental intoxication using Bothropoides jararaca venom. It was used Wistar rats that were randomly divided into 3 groups: C - control; VB - Bothrops venom + antivenom serum; and VBM - Bothrops venom + antivenom serum + Mikania glomerata. Cytokines were quantified in the serum and paw homogenate using ELISA test in three different moments (M1- 30 minutes, M2- 6 hours and M3- 24 hours after venom injection). The intoxication by Bothropoides jararaca venoms mainly stimulated the production of IL-6 in the serum and TNF-α, IL-1β, IL-6 in paw homogenate of animals experimentally intoxicated. Adjunctive treatment with the extract of the Mikania glomerata plant mainly influenced the production of IL-6, IL-10 and IFN-γ in the serum and IL-6, IL1β and IFN-γ in paw homogenate. Further research is necessary with the extract of Mikania glomerata in order to understand the action of this plant on the Bothropoides poisoning and also to verify the best way to manage it.

O presente estudo teve como objetivo quantificar os níveis de citocinas pró-inflamatórias, entre as quais TNF-α, interleucina-1β (IL-1β), IL-6, e anti-inflamatórias, como IL-10, interferon-γ (INF-γ), bem como comparar o efeito do tratamento convencional com o efeito do tratamento complementado pelo extrato da planta Mikania glomerata, na intoxicação experimental por Bothropoides jararaca. Foram usados ratos Wistar,divididos em três grupos: C - controle, VB - veneno botrópico + soro antiofídico e VBM - veneno botrópico + soro antiofídico + Mikania glomerata. As citocinas foram quantificadas, no soro e no homogenato desses animais, pelo teste ELISA, em três momentos (M1 - 30 minutos, M2 - seis horas e M3 - 24 horas após a inoculação do veneno). Os resultados obtidos evidenciaram que a intoxicação por veneno botrópico estimula principalmente a produção de IL-6 no soro e TNF-α, IL-1β, IL-6 no homogenato da pata de animais experimentalmente intoxicados. O tratamento complementar, com o extrato da planta Mikania glomerata, teve influência principalmente na produção de IL-6, IL-10 e IFN-γ no soro e IL-6, IL-1β e IFN-γ no homogenato. Porém, são necessários novos estudos com o extrato de Mikania glomerata para que se possa entender a ação dessa planta sobre a intoxicação botrópica, bem como verificar qual a melhor via para administrá-lo.
Quantification of cytokines in serum and paw homogenate of experimental intoxication for venom of the Bothropoides jararaca in Wistar rats treated with antivenom and Mikania glomerata
Keywords: Bothropoides jararaca; Mikania glomerata; ratos Wistar; citocinas; Bothropoides jararaca; Mikania glomerata; Wistar rats; cytokine